An Epidemiological-Association of Infant and Young Child Feeding Practices In Rural Area of Bareilly District: A Cross Sectional Study - Medhavi Agarwal; Akanksha Sinha; Rashmi Katyal (Medsci Publications, 2021)
Introduction: In developing countries, malnutrition is a major public health concern. Infant and young child feeding (IYCF) is a set of well-known, common and scientific recommendations for optimal feeding of newborn and children under two years of age including initiation of breastfeeding within one hour of birth, exclusive breastfeeding for first six months, after which appropriate and safe complementary foods should be given along with continuing breastfeeding up to two years of age and beyond. AIM: To find out the epidemiological association of IYCF practices in rural area of Bareilly district. Material and methods: The study was conducted in rural area of Bareilly, Uttar Pradesh from January 2020 to February 2020 in children aged ≤ 1 year. Results: There were significant associations (p< 0.05) between pre-lacteal feed and age of mother, sex of child, education of father and religion. Conclusion: There have been considerable developments in the status of IYCF practices in Bareilly. However exclusive breastfeeding was not fully practiced. Hence promotion of IYCF is needed.